Cooperative wind turbine control for maximizing wind farm power using sequential convex programming - Park, Jinkyoo; Law, Kincho H. (Energy conversion and management, 2015)
•The continuous wake model describes well the wake profile behind a wind turbine.•The wind farm power function describes well the power production of a wind farm.•Cooperative control increases the wind farm power efficiency by 7.3% in average.•SCP can be employed to efficiently optimize the control actions of wind turbines. This paper describes the use of a cooperative wind farm control approach to improve the power production of a wind farm. The power production by a downstream wind turbine can decrease significantly due to reduced wind speed caused by the upstream wind turbines, thereby lowering the overall wind farm power production efficiency. In spite of the interactions among the wind turbines, the conventional (greedy) wind turbine control strategy tries to maximize the power of each individual wind turbine by controlling its yaw angle, its blade pitch angle and its generator torque. To maximize the overall wind farm power production while taking the wake interference into account, this study employs a cooperative control strategy. We first derive the wind farm power as a differentiable function of the control actions for the wind turbines in a wind farm. The wind farm power function is then maximized using sequential convex programming (SCP) to determine the optimum coordinated control actions for the wind turbines. Using an example wind farm site and available wind data, we show how the cooperative control strategy improves the power production of the wind farm.